1992
DOI: 10.1182/blood.v79.7.1746.bloodjournal7971746
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD7-CD57+ T cells: a new T-lymphocyte subset expanded during human immunodeficiency virus infection

Abstract: CD7 and CD57 are two cell surface molecules related to the differentiation or functional stages of CD4+ T cells. The CD4+CD7- T cells represent a minor subset of CD4+ cells in normal individuals and are considered to contain the normal counterpart of Sezary T cells; the CD4+CD57+ peripheral blood lymphocytes (PBL) are detectable in long- term renal allograft recipients. We compared the cell surface expression of these CD7 and CD57 markers on CD4+ T lymphocytes in peripheral blood and lymphoid organs from norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…A substantial subpopulation of T cells has been reported to be CD7‐deficient under physiological ( 16,17 ) and certain pathological conditions, including autoimmune disorders and viral infection. ( 18–22 ) Consistent with these reports, the present study indicated that the proportion of CD4 + CD7‐ T cells in the peripheral blood of healthy adults is up to 10% (Fig. 1B,C).…”
Section: Discussionsupporting
confidence: 91%
“…A substantial subpopulation of T cells has been reported to be CD7‐deficient under physiological ( 16,17 ) and certain pathological conditions, including autoimmune disorders and viral infection. ( 18–22 ) Consistent with these reports, the present study indicated that the proportion of CD4 + CD7‐ T cells in the peripheral blood of healthy adults is up to 10% (Fig. 1B,C).…”
Section: Discussionsupporting
confidence: 91%
“…The protective immune response to TB infection is maintained by effector/memory CD4 + T cells that are stimulated by the persistence of mycobacterial antigen 4–7 . The presence of CD57 + T cells is associated with chronic antigenic stimulation 9–17 . This is the first study to demonstrate a significant increase of the CD4 + CD57 + T‐cell subset in the peripheral blood of patients infected with M. tuberculosis ; we also found, similarly to d'Angeac et al ., 24 who analysed healthy individuals, that the vast majority of these CD4 + CD57 + T cells showed a memory phenotype, as determined by their CD45RO expression 32 .…”
Section: Discussionsupporting
confidence: 83%
“…There are some pathological conditions in which antigen persistence is associated with the expansion of a CD4 + T‐cell subset bearing the CD57 marker, i.e. human immunodeficiency virus (HIV) infection, 9 renal or bone marrow allograft transplant, 10,11 chronic lymphocytic leukaemia, 12,13 colorectal cancer, 14,15 rheumatoid arthritis 16,17 and malarial infection 18 . CD57 is the sulfated polysaccharide SO 4 ‐3GlcAβ1,3Galβ1,4‐GlcNAc (also known as HNK‐1 or Leu‐7), which is present on several cell‐surface glycoproteins and glycolipids 19,20 and on unconventional T cells 10,18 .…”
Section: Introductionmentioning
confidence: 99%
“…This conundrum has been recently investigated by analyzing Tfh cells during HIV infection. Despite the progressive decline in total CD4 + T cells during HIV infection, an increase in Tfh cells (defined as either CD45RA − CXCR5 hi , CXCR5 + PD1 + Bcl‐6 + or CXCR5 + PD1 + CD4 + T cells in the LNs or CD57 + CD4 + T cells in the peripheral blood) was observed in HIV infected individuals 53 , 54 , 55 , 56 . This population of expanded T cells resemble bona fide Tfh cells as they express Bcl‐6, ICOS, CD40L and PD1, and secrete IL‐4, IL‐10 and IL‐21.…”
Section: Tfh Cells In Hivmentioning
confidence: 99%